2019
DOI: 10.1093/femsle/fnz174
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic degradation of 2-chloro-4-nitroaniline by Geobacter sp. KT7 and Thauera aromatica KT9

Abstract: 2-chloro-4-nitroaniline is a nitroaromatic compound widely used in industrial and agricultural sectors, causing serious environmental problems. This compound and some of its analogs were utilized by two Fe3+-reducing microbial strains Geobacter sp. KT7 and Thauera aromatica KT9 isolated from contaminated sediment as sole carbon and nitrogen sources under anaerobic conditions. The anaerobic degradation of 2-chloro-4-nitroaniline by the mixed species was increased approximately by 45% compared to that of individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…KT7 and Thauera aromatica KT9 cooperatively degraded 2-chloro-4-nitroaniline with an increased degradation rate compared to each species in isolation. 60 It was suggested that cross-feeding and nutrient sharing between the two species led to increased degradation. However, it has not been elucidated which enzymes contributed to the reduction of 2-chloro-4-nitroaniline.…”
Section: Discussionmentioning
confidence: 99%
“…KT7 and Thauera aromatica KT9 cooperatively degraded 2-chloro-4-nitroaniline with an increased degradation rate compared to each species in isolation. 60 It was suggested that cross-feeding and nutrient sharing between the two species led to increased degradation. However, it has not been elucidated which enzymes contributed to the reduction of 2-chloro-4-nitroaniline.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate a synergistic activity in the degradation of the parent compound and its metabolites by the microbial community in slurries. Previous studies have also indicated that the anaerobic degradation of complex organic compounds is mainly carried out by mixed cultures (Ghattas et al 2017;Duc 2019). The cooperation between microbial populations to degrade diuron and other metabolites in soil under aerobic conditions has also been described (Villaverde et al 2017).…”
Section: Identi Cation Of Metabolites Produced By Diuron Degradationmentioning
confidence: 99%
“…Native bacteria in sediment and soil bacteria had adapted to speci c conditions and exhibited synergistic interactions for herbicide degradation. The compatible bacterial strains can enhance the degradation of organic compounds (Duc 2019;Oanh and Duc 2021).…”
Section: Identi Cation Of Metabolites Produced By Diuron Degradationmentioning
confidence: 99%
“…One product was formed after chlorination and long time storage. Remarkably, 4-nitroaniline was the major product formed for all the degradation processes and also the most mutagenic product (Franco et al, 2018); (Duc, 2019). That is, in a water treatment plant, the dye would probably not be detected, because sunlight and chlorination promote its degradation drastically.…”
Section: Detection Of Ab210 and Degradation Products By Lc-ms/msmentioning
confidence: 99%